Validation of a Knowledge Test in Turkish Patients on Warfarin Therapy at an Ambulatory Anticoagulation Clinic - OKUYAN, BETÜL; SANCAR, MESUT; AY, NADİYE PINAR (TURKISH PHARMACISTS ASSOC, 2021)
Objectives: This study aimed to evaluate the validity and reliability of an oral anticoagulation knowledge (OAK) test in Turkish patients on warfarin therapy at an anticoagulant outpatient clinic. Materials and Methods: This study was conducted at an ambulatory anticoagulation clinic and included patients older than 18 years who had been using warfarin for at least six months. Patients' demographic and clinical data were collected. Internal consistency was calculated using the Kuder-Richardson 20 (KR-20) coefficient, and the test-retest reliability of the Turkish version of the OAK test was assessed. Results: Patients' mean age was 59.83 +/- 11.93 (26-90) years (n=240; 133 women). The mean score of the OAK test was 14.19 +/- 3.01. The test-retest reliability of the scale (n=30) was moderate for the total score (p<0.001). The KR-20 value, a measure of internal consistency, was 0.671. Patients of a younger age and higher educational level were more likely to have higher levels of anticoagulation knowledge than patients of an older age and lower education level (p<0.05 for both comparisons). Conclusion: The Turkish version of the OAK test can be used to determine the patients' knowledge on oral anticoagulation.
Keywords: Warfarin; anticoagulant; knowledge; pharmacist; ADHERENCE; ASSOCIATION; TRIAL